Research on Autonomous Driving Control Technology for Heavy Haul Train - DU Kaibing; ZHANG Zhengfang; WEN Yuliang (Kongzhi Yu Xinxi Jishu)
In traditional heavy haul train operation, which is generally in manual control mode, the difficulty for drivers to operate the heavy haul train is increased and the work intensity is high. In order to further improve transportation throughput, save cost, reduce drivers’ work intensity, a control method considering railway lines and signals was proposed. A distributed longitudinal dynamic model, resistance model and air braking model of a long freight train are established for the control system. The target status dynamic planning and control technology under multiple constraints is studied. Autonomous driving control experiments are successfully conducted in Xikang Railway. Automatic zero-speed starting, acceleration control, deceleration control, air braking control, air braking control, passing through neutral zone and automatic stopping to zero-speed have been successfully achieved with the proposed technology. Experimental results show that autonomous driving of the heavy haul train can be effectively realized by the method proposed in this paper.